The Role of Virtual Reality and Augmented Reality in Sports Psychology: Advancements, Applications, and Implications - Zekeria Baye; Kassa Yusuf, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The essential purpose of this research study is to determine the role of virtual and augmented reality in sport psychology. Research determines the advancements, applications, and implications of virtual and augmented reality. According to the research, virtual and augmented reality are the main independent variables. Sports psychology is the dependent variable for determining the research using secondary data. These data were collected from different websites related to variables. These data are based on numerical form. For this purpose, I used E-views software to determine the results. Descriptive statistic analysis, correlation coefficient analysis, unit root test, and equality test analysis also explain the co-integration test between virtual and augmented reality. The overall result found a significant impact of virtual reality in sport psychology. Augmented reality shows positive and significant relation in sport psychology.